Geology and Sedimentology of Gua Cha, Gua Musang, Kelantan. - Lum, Su Zan (2015)
Gua Cha is located in the western of Gua Musang District, Kelantan. It represents series of Gua Musang Formation which aged Middle Permian to Upper Triassic. It predominantly consists of laminated limestone, interbedded with shale at the foothill. The dark grey and milky white limestone here indicates the process of metamorphism in the area Two (2) types of sampling method had been done for this sedimentology research, which were systematic sampling and random sampling. Based on the petrographical studies, there are four (4) types of limestone in the study area. namely ferroan calcitic dismicrite, calcitic pelsparite, calcitic oosparite and calcitic dismicrite. These occurrences suggest that the study area was deposited under Gua Musang Formation, which were shallow marine environment. From the aspect of diagenesis. the processes involved were compaction and cementation. dissolution and dolomization.